PRODUCTION PERFORMANCE OF MALE LOCAL DUCKS (ANAS PLATHYRINCHOS) FED TORCH GINGER FLOWER (ETLINGERA ELATIOR) SOLUTION INCLUDED IN COMMERCIAL RATION - Supriatman, Pepi; Dihansih, Elis; Anggraeni, Anggraeni (Universitas Djuanda Bogor, 2017)
The needs for animal protein increase significantly as the number and prosperity level of people increase. Ducks are water poultry that can be used to supply meat and eggs to fulfill people need for protein. Ducks are the second most important egg producers after chickens. In Indonesia, duck eggs share about 30-40% of total egg supply (Suharno 2002). This study was aimed at assessing the production performance of male local ducks fed torch ginger flower (Etlingera elatior) solution included in commercial ration. Male local ducks aged 2 weeks with average initial body weight of 450 g were used. Commercial feed was mixed with torch ginger flower solution. A completely randomized design with 4 treatments and 3 replicates was used. Treatments consisted of four levels of torch ginger flower solution, namely 0, 2.5, 5.0, and 7.5%. Data were subjected to an analysis of variance and measurements were taken on feed intake, body weight gain, feed conversion, and mortality rate. Results showed that no significant differences (P>0.05) were found in all parameters measured. The average feed intake was 4037.67±205.748 g, body weight gain was 1034.79±129.14 g/head, and feed conversion was 3.94±0.45. The mortality rate was found to be 0% indicating no bird was found died in all treatment groups. Provision of commercial feed with a mixture of a solution of interest ginger flower is not able to improve the performance of male local ducks.Key words: animal protein, water poultry, feed intake, body weight gain, feed conversion.